Rancang Bangun Sistem Informasi Peminjaman dan Pengembalian Buku di Perpustakaan SMK Lugina Rancaekek - Ricky Rohmanto; Indri Tri Julianto; Tria Afini (Masoem University, 2023)
The system of borrowing and returning books at the Library of SMK Lugina Rancaekek includes making loan reports, return reports, and member data is still done manually in the ledger, so errors often occur so that making reports takes a long time. The method used in this is the SLDC (System Development Life Cycle) method using Waterfall. Analysis and design of the system uses other tools such as Data Flow Diagram, Flowmap, Structure Chart, E-R Diagram, Data Dictionary, while the implementation uses Microsoft Visual Foxpro 9.0 and Microsoft Database Foxpro 9.0 for Database. The design of this system can facilitate the search for book data, speed up report generation, make it easier to control book stock, facilitate the process of borrowing and returning books so that they can produce information more quickly, precisely and accurately.